Clinical and biological roles of Kelch-like family member 7 in breast cancer: a marker of poor prognosis - Kurozumi, Sasagu; Joseph, Chitra; Sonbul, Sultan; Gorringe, Kylie L.; Pigera, Marian; Aleskandarany, Mohammed A.; Diez-Rodriguez, Maria; Nolan, Christopher C.; Fujii, Takaaki; Shirabe, Ken; Kuwano, Hiroyuki; Storr, Sarah; et al. (Springer, 2018)
Background: The functions of many proteins are tightly regulated with a complex array of cellular functions including ubiquitination. In cancer cells, aberrant ubiquitination may promote the activity of oncogenic pathways with subsequent tumour progression. Kelch-like family member 7 (KLHL7) is involved in the regulation of ubiquitination and may play a role in breast cancer (BC). Present study aims to evaluate the biological and clinical usefulness of KLHL7 in BC utilising large well-characterised cohorts with long-term follow-up. Methods: The relationships between KLHL7 gene copy number alteration (CNA) and mRNA expression and clinicopathological variables and clinical outcomes were evaluated in 1980 patients from the METABRIC BC cohort. Prognostic signifcance of KLHL7 mRNA was validated using the Breast Cancer Gene-Expression Miner v4.0 datasets (n=5206). KLHL7 protein expression was assessed using immunohistochemistry in a large annotated series of early-stage BC (n=917) with long-term follow-up. Results: KLHL7 CNA was signifcantly correlated with its mRNA expression. KLHL7 mRNA expression was higher in luminal B and basal-like molecular subtypes and in higher grade tumours. Increased KLHL7 protein expression was signifcantly correlated with features of aggressive phenotype including lymphovascular invasion, high histological grade, hormonal receptor negativity, high PIK3CA and p53 expression. Outcome analysis showed that high KLHL7 expression is an independent predictor of shorter survival (p=0.0011). Conclusions: KLHL7 appears to play an important role in BC progression. High KLHL7 protein expression identifed a subgroup of BC with aggressive behaviour and provided independent prognostic information.